PREVALENCE, PRACTICE, PERCEPTION OF SELF-MEDICATION PATTERN AMONG MEDICAL STUDENTS - GOEL, DIVYA (International Journal of Current Pharmaceutical Research, 2021)
Objective: The use of drugs (prescription as well as non-prescription by the individual for treating self-diagnosed conditions/symptoms is a practice prevalent all around the world, though the extent, the reason may vary. The practice of self-medication is increasingly becoming a part of self-care. If practiced properly and with the authentic knowledge of drugs, it can save resources such as time and money. However, its improper use may lead to various health problems like adverse drug reactions, prolonged suffering, and drug-dependence and increase resistance among various pathogens. It has many implications, especially among medical students who have some knowledge and exposure to drugs and can present a serious threat to professionalism in medicine and it has the potential to put at risk public trust into this profession. The aim of this research was to assess the knowledge, attitude and practice of self-medication among medical students. Methods: Research was performed as a cross-sectional study and it included 150, 2nd year (4th semester) students of a medical college. Students filled out a questionnaire created for the purpose of this research and consisted of both open-ended and close-ended questions about demographic and self-medication Consenting students anonymously filled the questionnaire. Questions about self-medication were related to the period of the previous three months. Results: Out of 150 filled questionnaires, data of 126 were analysed as twenty-four Questionnaires were incomplete. 90.47%% medical students were found to practice self-medication. Symptoms for which they took the drugs for self-medication were fever (49.68%) followed by headache, common cold/cough and pain abdomen. Drugs taken by them for self-medication were Paracetamol (85.79%), antibiotics (77.54%), analgesics, Antihistaminic and cough suppressants. Ease (43.65%) was cited as the main reason for self-medication by the respondents. Most common source of drug information was their experience in the past illness (54.03%) Of the respondents 90.48% knew about adverse drug reactions and 93.65% knew about drug-drug interactions. Conclusion: This study shows that the practice of self-medication is rampant among medical students of the institute. In this situation, awareness should be created toward appropriate antibiotic usage and the practice of responsible self-medication needs to be promoted among future healthcare providers. Furthermore, stringent implementation of laws governing the sale of prescription medicines can help in limiting the self-medication practice.